2010
DOI: 10.1167/10.5.23
|View full text |Cite
|
Sign up to set email alerts
|

Attentional cueing: Fearful body postures capture attention with saccades

Abstract: According to theories of attention and emotion, threat-related stimuli (e.g., negative facial expressions) capture and hold attention. Despite these theories, previous examination of attentional cueing by threat showed no enhanced capture at brief durations. One explanation for the absence of attentional capture effects may be related to the sensitivity of the manual response measure employed. Here we extended beyond facial expressions and investigated the time course of orienting attention towards fearful bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…This account is consistent with results from previous cueing studies. In these studies, an eye movement had to be made to one of two target locations that were previously cued with threatening or nonthreatening stimuli (Bannerman et al, 2010a(Bannerman et al, , 2010bSchmidt, Belopolsky, & Theeuwes, 2015). Both studies showed the tight coupling between a shift of spatial attention to a threatening stimulus and the direct influence on the oculomotor system.…”
Section: Attentional Capture and Disengagementmentioning
confidence: 99%
See 1 more Smart Citation
“…This account is consistent with results from previous cueing studies. In these studies, an eye movement had to be made to one of two target locations that were previously cued with threatening or nonthreatening stimuli (Bannerman et al, 2010a(Bannerman et al, , 2010bSchmidt, Belopolsky, & Theeuwes, 2015). Both studies showed the tight coupling between a shift of spatial attention to a threatening stimulus and the direct influence on the oculomotor system.…”
Section: Attentional Capture and Disengagementmentioning
confidence: 99%
“…Both studies showed the tight coupling between a shift of spatial attention to a threatening stimulus and the direct influence on the oculomotor system. For example, Bannerman et al (2010aBannerman et al ( , 2010b showed that a briefly presented threatening peripheral cue decreased saccade latency relative to a nonthreatening cue when an eye movement had to be executed to a target presented at the same location (valid cue) and increased saccade latency when the target was presented at the opposite location (invalid cue). Likewise, Schmidt et al (2015) showed that a peripherally presented threatening stimulus interfered with subsequent endogenously driven saccades; a decrease in saccade latency when a saccade had to be executed to the location previously cued with a threatening stimulus relative to a nonthreatening stimulus, and an increase in saccade latency when a saccade had to be executed away from that location.…”
Section: Attentional Capture and Disengagementmentioning
confidence: 99%
“…In fact, an experiment by Bannerman, Milders, and Sahraie (2010) that reported attentional capture by fearful postures also revealed impaired disengagement in an exogenous cueing task at the shortest cue duration (20 ms). However, their study only looked at individuals reporting normal levels of trait anxiety, potentially missing any information regarding the modulatory role of anxiety that has so often been seen in prior investigations.…”
mentioning
confidence: 97%
“…On invalid trials, state-anxious individuals took longer to respond when the cue was an angry face as opposed to a neutral or happy face, suggesting difficulty in disengaging attention from threatening facial expressions. Delayed disengagement has also been observed in response to threat-related words (Fox, Russo, Bowles, & Dutton, 2001), fearful faces (Georgiou et al, 2005), and more recently, direct facing threatening postures (Bannerman, Milders, & Sahraie, 2010). Although often seen only in anxious populations, Belopolsky, Devue, and Theeuwes (2011) found impaired disengagement of overt attention from angry faces in the general population using eye tracking, a measure with greater sensitivity than the more traditionally used measure of manual reaction time.…”
mentioning
confidence: 98%
“…Evidence from visual search paradigms reveal an advantage in the rate and accuracy for detecting threatening faces amongst distractors compared to neutral or happy faces (Öhman, Lundqvist, & Esteves, 2001), as well as for snakes and spiders (Öhman, Flykt, & Esteves, 2001) and threatening postures (Bannerman et al, 2010;Gilbert, Martin, & Coulson, 2011). Because of attentional mechanisms that are efficient and automatic (Pratto & John, 1991), humans are particularly well suited for detecting threat in the environment.…”
mentioning
confidence: 99%